2013
DOI: 10.1016/j.seizure.2012.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Role of CYP2C9 polymorphism in phenytoin-related metabolic abnormalities and subclinical atherosclerosis in young adult epileptic patients

Abstract: Our study indicates that young epileptic patients with the CYP2C9 polymorphism gene have a low risk of subclinical atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…All four variants were inherited from his father who was also diagnosed with CAE. EFHC1, CYP2C9 , and RYR2 genes are known to be implicated in epilepsy454647. KCNN4 encodes a member of calcium-activated potassium channels.…”
Section: Resultsmentioning
confidence: 99%
“…All four variants were inherited from his father who was also diagnosed with CAE. EFHC1, CYP2C9 , and RYR2 genes are known to be implicated in epilepsy454647. KCNN4 encodes a member of calcium-activated potassium channels.…”
Section: Resultsmentioning
confidence: 99%
“… 39 Previous studies found that CYP2C9 gene polymorphisms are associated with serum TC and LDL-c levels in young adult patients with epilepsy. 12 In humans, the CYP2C19 gene expression level is about 10% of the CYP2C9 gene, but these two genes have 91.2% sequence uniformity. 40 Recently, studies have found that EETs and CYP2C19 were upregulated in triple-negative breast cancer (TNBC) tumors, which correspond to the fatty acid binding proteins, adipocyte signaling, and metastasis-related processes, which preliminarily confirmed the role of CYP2C19 gene’s endogenous metabolic regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Variations within the CYP2C9 gene have also shown associations with phenytoin-related adverse reactions. Phenytoin is primarily metabolized to its inactive form by CYP2C9, and alleles that result in decreased enzymatic activity, specifically CYP2C9*2 and *3 , have been linked with increased phenytoin concentrations [135-138] and an increased risk for neurological toxicities [139, 140] and cutaneous adverse drug reactions [133, 141]. Consideration of both HLA-B*15:02 and CYP2C9*2 and *3 may be important in any future clinical pre-treatment screening programs.…”
Section: Important Variantsmentioning
confidence: 99%